'My heart tears' and 'my eyes open': Exploring the verb te 'to tear' and its range of interpretations in Asante-Twi. (10th September 2021) - Agyepong, Dorothy
Abstract : Events of tearing in Asante-Twi (Akan, Niger-Congo, Kwa) are described with two verbs, te 'to tear' and suane 'to tear lengthwise'. The former is generic and describes all forms of tearing. The latter, which is more specific, describes tearing events that are carried out in a lengthwise manner (Agyepong, 2017). Characteristic of verbs, te and suane combine with different objects to derive a range of interpretations that can be categorized as literal or figurative. In this paper, I explore the ways in which te 'to tear' (in particular) interacts with different objects to generate an array of contextualised interpretations. The discussion of the verb and its interpretations are based on three theoretical assumptions. First, from a monosemic-bias perspective (Ruhl, 1989), I espouse a single invariant sense for te and demonstrate that all other interpretations are derived contextually. Second, I propose a three-level semantics (Wilkins and Hill, 1995) relevant for the derivation of the various interpretations of the verb. Third, I show that distinct syntactic constructions (Goldberg, 1995) in which the verb and its arguments occur are key to generating online interpretations. The analysis is based on data gathered from written literary texts, dictionaries, Bible translations, and stimulated-ethnographic interviews with native speakers. I supplement these with constructed examples based on my intuition as a native speaker of Asante-Twi.